Reproductive performance of traditionally managed sheep in the south western part of Ethiopia - Berhanu, Belay; Haile, Aynalem (2009)
The study was conducted to assess the reproductive performance of ewes under village management condition in south western part of Ethiopia. The study was a monitoring study which took place for three years (1995-1997). The overall least squares means for lambing interval (LI) and annual reproductive rate (ARR) were 262 ±53.4 days and 1.88 ± 0.44, respectively. The overall least squares means of age at first lambing and litter size were 404 + 65.40 day and 1.21+1.45 lambs, respectively. Lambing interval was significantly (P<0.05) influenced by parity of the ewe, type of birth and year of lambing. The ewes at their first, and six and above parity showed longer subsequent lambing interval than ewes at 2-5 parity. Ewes that suckled singles had shorter subsequent lambing interval than ewes which suckled twins (255+3.74 vs 283+5.72 days). Year of lambing and type of birth exerted a significant effect (P<0.05) on ARR. The ewes that dropped twins had higher ARR than ewes which dropped singles (1.52 Vs 2.56 lambs/ewe/year). Litter size was significantly (p<0.05) influenced by season of lambing and parity of the ewe. There was a tendency that, litter size increased with an increase of parity up to fifth parity and dropped at the sixth and more parities. The reproductive performance of ewes under village management condition is discussed in association with reports elsewhere in the tropics.